The Effect of Customer Experience and Brand Trust on Customer Loyalty Steaky Steak Bandar Lampung - Samudra, Ambia; Warganegara, Tri Lestira Putri (Dinasti Publisher, 2024)
Customer loyalty is one of the important aspects that needs to be considered by every company in order to retain existing customers. Companies can increase customer loyalty by improving customer experience and fostering brand trust. The purpose of this study was to determine the effect of customer experience and brand trust on customer loyalty. The population of this study were all consumers of Steaky Steak Bandar Lampung. The sample in this study amounted to 100 respondents who were customers of Steaky Steak Bandar Lampung. The sampling technique in this study was simple random sampling. The independent variables in the study are customer experience and brand trust, customer loyalty as the dependent variable. Multiple regression analysis, along with the t-test and f-test, is the method used in this study. Based on the research results, customer experience has a positive and significant effect on customer loyalty, brand trust has a positive and significant effect on customer loyalty, customer experience and brand trust together have a positive and significant effect on customer loyalty Steaky Steak Bandar Lampung.